Information Systems and Industrial Resource Planning - Nova Suparmanto; Heri Nurdiyanto; Anisa Kharismawati (Utan Kayu Publishing, 2025)
Information Systems (IS) and Industrial Resource Planning (IRP) play a critical role in the optimization and management of industrial operations in today's fast-paced and technology-driven environment. Information Systems encompass a range of technologies and practices designed to collect, store, process, and distribute information within an organization, facilitating decision-making and process automation. Industrial Resource Planning, on the other hand, is an integrated approach to managing the resources required in manufacturing processes, including raw materials, human resources, machinery, and financial assets. The primary objective of IRP is to ensure that industrial operations are carried out efficiently and cost-effectively, with minimal waste and maximum productivity. The integration of IS and IRP allows organizations to better track resources, improve production schedules, and enhance supply chain management. By utilizing data analytics and advanced information technologies, companies can predict demand fluctuations, optimize inventory management, and reduce downtime. Furthermore, IS and IRP systems often incorporate real-time monitoring tools, enabling managers to make informed decisions based on up-to-date information about the production process. This leads to improved overall performance and the ability to respond to challenges quickly and effectively. An essential component of IRP is its ability to forecast and plan for future resource needs based on historical data and industry trends. By leveraging IS tools, such as enterprise resource planning (ERP) software, manufacturers can automate their resource allocation and streamline production processes. The alignment of IS and IRP contributes to achieving sustainability goals, as resource utilization can be carefully monitored and adjusted to minimize environmental impact. As industries continue to evolve with the advent of Industry 4.0 technologies, the role of IS and IRP systems will only grow in significance, shaping the future of manufacturing and industrial operations. The paper highlights the importance of these systems in modern industrial settings and explores their impact on operational efficiency, resource management, and strategic decision-making..